Dietary fiber consumption of urban Costa Rican population - Gómez Salas, Georgina (2021)
Abstract: The consumption of dietary fiber is essential for intestinal health, and has been associated with a lower risk of coronary heart disease, stroke, stroke, hypertension, obesity, and diabetes. The objective of this study was to analyze the consumption of total, soluble and insoluble dietary fiber according to the sociodemographic characteristics and to analyze the fiber source foods in the urban Costa Rican population that was part of the Latin American Study of Nutrition and Health (ELANS). Consumption of total, soluble and insoluble dietary fiber was analyzed in 798 people aged 15 to 65 years, residents of urban areas of the country, by means of two 24-hour recall. In addition foods sources of fiber were identified in the population. Mean consumption of dietary fiber is lower than the recommendation, being higher in men and in people with lower body mass index and waist circumference. The main source of total fiber and insoluble fiber were beans, while coffee constitutes the main source of soluble fiber. The urban Costa Rican population consumes an amount of dietary fiber that is lower than the recommendation. It is important to encourage the consumption of fiber-source foods such as beans, fruits, vegetables and whole grains to improve digestive health and reduce the risk of chronic diseases.